Key Thinkers in Cross- Cultural Communication - Nurmatova Kamola Alisher qizi; Djuraeva Madina (Journal of Innovation in Education and Social Research, 2023)
This article examines the perspectives of three choosen cross-cultural communication researchers and evaluates the importance and practical relevance of their work. Geert Hofstede, Edward T. and Mildred R. Hall are three of the prominent thinkers mentioned. In this article, their main theories are surveyed, along with the benefits and drawbacks of each, and how they might be used to explain how culture affects people. Moreover, examples are given to help clarify the topic. One of the most well-known and influential researchers in the area of cross-cultural communication is Geert Hofstede, followed by Edward and Mildred Hall. They have constructed a large portion of the theoretical framework that cross-cultural analysis is based on. These key concepts offer a fundamental theoretical and practical approach to a greater understanding of the relationship between culture and communication and are frequently complementary. This article seeks to evaluate their most important research and demonstrate how the results might be used.